Guidelines to design organic electrolytes for lithium-ion batteries: environmental impact, physicochemical and electrochemical properties. Issue 8 (27th March 2017) - Flamme, Benjamin; Rodriguez Garcia, Gonzalo; Weil, Marcel; Haddad, Mansour; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie; Chagnes, Alexandre
Abstract : Electrolytes for lithium-ion batteries (LiBs) have been put aside for too long because much efforts have been done on electrode materials. Abstract : Electrolytes for lithium-ion batteries (LiBs) have been put aside for too long because a few new solvents have been designed to match electrolyte specifications. Conversely, significant attention has been paid to synthesize new electrode materials and especially positive electrodes. Particularly, most of the studies dedicated to the investigation of electrolytes for LiBs have been focused on mixing different molecules. Currently, the development of high-voltage materials for LiBs stimulates the synthesis of new solvents and new salts that are more stable against oxidation. Despite the challenges, only a few teams are active in this field in developing a rational approach combining physicochemistry, electrochemistry and modelling from the molecular to the macromolecular levels. After assembling a critical collection of physicochemical and electrochemical data from the literature, this study highlights the main trends between the chemical structure of the organic dipolar aprotic solvents and their physicochemical and electrochemical properties to provide a guide for chemists to design new electrolytes for LiBs. This guide also includes indicators to take into account the environmental impact of solvent production by including a life cycle assessment of eight different solvents.